القص النسائي السّوريّ حتى التسعينيات - مغربي, فاروق; مرعي, رودان (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
تعدّ القصة القصيرة في سورية من أكثر الأجناس الأدبية إنتاجاً, فقد كثر كتّابها, وتعدّدت أنماطها, واستعصى تصنيفها, وقد مرّت بأطوار متلاحقة, أسهمت المرأة إسهاماً كبيراً في صنع مشهدها المكتظّ بكلّ غثٍّ وسمين, ويأتي هذا البحث بوصفه قراءة تأريخية نقديّة للمنتج القصصي النسائي السوري منذ نشأته الأولى في الأربعينيات من القرن العشرين حتى أواخر الثمانينيات منه, ليقول كلمته في تجارب مشهورة وأخرى مغمورة, ولينتهي إلى استنتاج عام في تلك التجارب بوصفها تدور في فلك المنجز والتقليدي وتأخذ لبوساً نسوياً في مساربها الموضوعية. Short story in Syria is considered one of the most prevalent exiting literary genres. Its writers were many, with a plenty of styles. It is difficult to categorize, having gone through many stages. Women writers contributed to the development of short story writing and produced stories ranging in their value. This research is a historical and critical reading of Syrian women narrative writing from its beginning in 40th till the end of 80th of 20th century. It judges the experiments of those women writers, emphasizing the point that most of their writing by women is still traditional, though it seeks to appear feminist in nature.